The effect of family-spouse adjustment on expatriate adjustment: Malaysia as a host country / Noor Hafiza Zakariya...[et al.] - Zakariya, Noor Hafiza; Othman, Abdul Kadir; Abdullah, Zaini (Universiti Teknologi MARA, Kedah, 2019)
Multinational corporations (MNCs) tend to employ and send their expatriates to other countries known as host countries to manage international businesses. Once expatriates could adapt and adjust themselves to the host countries, perhaps in return would enhance their job performance. Normally, expatriates are accompanied by their spouse and family members in the host countries. They could be a major influencer to expatriate adjustment during the accomplishment of the international assignments at the host country. Thus, the purpose of this study is to investigate the effect of the family-spouse adjustment on expatriate adjustment in the host country, Malaysia. This study adopted a quantitative method with purposive sampling. Based on the result of 139 expatriates who are working at MNCs in Malaysia, family-spouse adjustment significantly influences expatriate adjustment. Therefore, MNCs should consider this factor in managing expatriates’ adjustment in the host country. Also, this study would promote new insights for international human resource management field and cross-cultural managements’ scholars and practitioners.